Prevalence of post-stroke depression and its relationship with risk factors for stroke - Farhad Iranmanesh; Reza Vazirynejad; Faranak Gadari; Najmeh Rajabpoor (Fasa University of Medical Sciences, 2012)
Background & Objective: Stroke is a major public health problem. Post-stroke depression is one of the common emotional disorders afflicting stroke survivors. The purpose of this study was to determine of the prevalence of depression and its relationship with risk factors for stroke after an episode of stroke. Materials & Methods: This descriptive study was performed on 100 consecutive patients with acute ischemic stroke admitted to Ali Ebn Abitaleb hospital in Rafsanjan .The diagnosis of acute ischemic stroke was made by a neurologist and confirmed by MRI. Frequency of depression, according to DSM-IV criteria, as well as demographic data and risk factors for stroke were registered and analyzed by T test ، Chi Square and Fishers Exact Tests. Results: % 59 of patients suffered depression. The frequency of depression was significantly higher in women (38%) than men (21%). There was no significant relation between depression and age and risk factors for stroke. Hypertension (65%), diabetes (50%) and hyperlipidemia (40%) were the most common risk factors. Conclusion: Generally, our results show that post stroke depression is prevalent in our society, and this is more prominent among women. Early diagnosis and treatment can help to improve quality of life of these patients.